2021
DOI: 10.1080/22221751.2021.1933608
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of novel reassortant mammalian orthoreovirus from pigs in the United States

Abstract: Mammalian orthoreovirus (MRV) infects multiple mammalian species including humans. A United States Midwest swine farm with approximately one thousand 3-month-old pigs experienced an event, in which more than 300 pigs showed neurological signs, like “down and peddling”, with approximately 40% mortality. A novel MRV was isolated from the diseased pigs. Sequence and phylogenetic analysis revealed that the isolate was a reassortant virus containing viral gene segments from three MRV serotypes that infect human, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 52 publications
(74 reference statements)
0
20
0
Order By: Relevance
“…In this study, while searching for porcine enteric viruses in Japan, we isolated five MRVs from 230 fecal samples of pigs with or without diarrhea by culturing them in MA-104 cells. Several other cell lines, including African green monkey kidney (Vero) cells [13-15, 19, 30-33], Madin-Darby Canine Kidney cells [16], primary porcine kidney cells [18], Madin-Darby bovine kidney cells [29], swine testicular cells [34], and N1380 cells [35],…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, while searching for porcine enteric viruses in Japan, we isolated five MRVs from 230 fecal samples of pigs with or without diarrhea by culturing them in MA-104 cells. Several other cell lines, including African green monkey kidney (Vero) cells [13-15, 19, 30-33], Madin-Darby Canine Kidney cells [16], primary porcine kidney cells [18], Madin-Darby bovine kidney cells [29], swine testicular cells [34], and N1380 cells [35],…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, porcine MRV infections are considered asymptomatic in most cases. However, severe diarrheic outbreaks I pigs caused by MRV alone or co-infection with other pathogens have been reported in China, South Korea, the United States, and Italy [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Cross‐species transmission of bat MRVs infecting humans has also been documented 7,16–18,47,48 . Although MRVs have been detected in many species in the United States, including human, swine, bovine, bats, and deer, 11,14,18,20,21 the prevalence of MRVs and what kind of MRVs exist and circulate in bats in North America are poorly understood. In this study, we screened more than 900 bats collected in the United States and found that 4.4% of collected bats including 40 big brown bats and 1 red bat were positive to MRV; these bats were collected from Nebraska, Kansas, and Missouri.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we also tested the infection of isolated MRVs in primary or immortalized respiratory cell lines from different species including bat lung cells, swine immortalized NEC, swine BEC, and ferret TEC, which were infected with each virus at an MOI of 0.05, and the supernatants from each infected cell line were collected at 24 and 48 h postinfection (hpi). Virus titer was determined by the immunofluorescence assay using an anti‐reovirus capsid protein μ1C monoclonal antibody (10F6; DSHB) and the FITC‐labeled goat anti‐mouse IgG second antibody as described previously 21 …”
Section: Methodsmentioning
confidence: 99%
“…MRV1 to 3 serotypes were isolated from pigs in worldwide [8,16,17,19,39] including Japan [6,7,11]. Some studies have shown that MRVs isolates caused severe symptoms and mortality in experimentally infected piglets and pigs [32,36], which means that MRVs have the potential to cause serious problems on swine industry. Although data on the surveillance in pig farms can help to control MRVs infection among pigs, the surveillance report in Japan is limited.…”
Section: Introductionmentioning
confidence: 99%